QRIS-Based Payment System at Loddy's Pet Shop Cirebon - Kosim Kosim; Asep Kosasih; Angel Imannuel (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The development of information technology encourages business actors to shift from manual systems to more efficient computerized systems. Loddy’s Pet Shop Cirebon still uses manual (non-computerized) transaction recording, which is prone to human error, data loss, and delays in financial reporting. This research aims to design and implement a payment system based on the Quick Response Code Indonesian Standard (QRIS), integrated with the store’s cashier system, to facilitate transaction processing and financial recording. The research method used is descriptive, with data collection techniques including observation, interviews, and literature study, while the system development adopts the Rapid Application Development (RAD) method. The system is built using PHP and MySQL and integrated with the Midtrans payment service to generate dynamic QRIS codes. The implementation results show that the system can minimize recording errors, accelerate payment processes, generate financial reports automatically, and improve operational efficiency. With this system, Loddy’s Pet Shop can enhance service quality and gain a competitive advantage in the digital era.